Pengaruh Perbedaan Dosis Minyak Ikan Dan Minyak Jagung Terhadap Aktivitas Enzim Pencernaan Dan Pertumbuhan Ikan Kelabau (Osteochilus melanopleurus) - Hutasuhut, Abdul Rahman; Susanto, Adi; Kusdianto, Heru (Jurnal Akuakultur Sungai dan Danau, 2024)
The purpose of this study was to examine the effects of two lipid sources dosages on the digestive enzymes activity and growth of Kelabau (Osteochilus melanopleurus). In this study, there were five treatments and three replicates in a completely randomised design (CRD). In this investigation, the following dosage ratios of fish oil and corn oil were used as treatments: A (100%:0%), B (75%: 25%), C (50%:50%), D (25%:75%), and E (0%:100%). The experimental fish had initial average length of 5â€“6 cm and weight of 2.8â€“3.6 g. Fish were reared for 45 days in plastic tanks measuring 34.3 cm x 38 cm x 31.5 cm using a recirculation system. Each tank was filled with 25 liters of water and the fish stocking density was 20 fish/tank. Fish are fed twice daily on an at-satiation basis, in the morning and the evening. Data analysis was carried out using the analysis of variance (Anova) with a confidence level of 95% and continued with the Duncan Multiple Range Test (DMRT). The findings demonstrated that the activity of digestive enzymes (amylase, lipase, and protease) was significantly (P<0.05) impacted by the differences in the content of the two lipid sources, with an increase in the percentage of corn oil causing an increase in the activity of all digestive enzymes. Conversely, neither growth nor specific growth rate were significantly affected (P>0.05) by the variation in the percentage of the two lipid sources. But in contrast to the other treatments, treatment A resulted in more growth. The reason for this could be because the ingredients were adequate to meet the fatty acid requirements for Kelabau fish growth, therefore the fatty acid addition was no longer necessary.Â